The Effect of Korean Brand Ambassador and Customer Online Review on Purchase Decision with Brand Image as An Intervening Variable - Muhasanah, Rodhiyah; Syilfiana, Intan; Juliyah, Juliyah (Lafadz Jaya Publisher, 2024)
This study aims to analyze the effect of Korean Brand Ambassadors and Online Customer Reviews on purchasing decisions for YOU Beauty skincare products in Jakarta, with Brand Image as a mediating variable. This study uses a quantitative approach to examine the direct and indirect relationships between the variables studied. The path analysis technique was applied to process the data collected. The results showed that Korean Brand Ambassador has a positive and significant influence on purchasing decisions, while Online Customer Review does not have a significant positive influence on purchasing decisions. These findings highlight the important role of Brand Image in strengthening the relationship between Korean Brand Ambassadors and Online Customer Reviews with purchasing decisions, especially in the skincare product industry.